Peningkatan Interaksi Sosial dengan Layanan Bimbingan Kelompok Menggunakan Media Zoom - Della Angraini; Dosi Juliawati; Hengki Yandri (Universitas Ahmad Dahlan, 2021)
Increased Student Social Interaction with Group Guidance Services Using Zoom MediaSocial interaction has become a serious problem nowadays, with the development of internet media today, students have interacted more with gadgets than interacting directly face to face with their friends. So the purpose of this study is to try to improve student social interaction through group guidance services using the zoom meeting application. This study uses an experimental approach with the type of one group pre-test post-test design with the student population of Madrasah Tsnawiyah Negeri 5 Kerinci, then the determination of research subjects is carried out with purposive sampling techniques taken from the results of pre-test with a total of 16 students. The data collection instrument uses Social Interaction Scale (SIS). Data that has been collected in the analysis descriptively and to see changes in students' social interaction before after being given group guidance services using Wilcoxon Signed Rank Test analysis. The results of this study revealed that group guidance services use effective zoom media to improve students' social interaction.